Behavioral, physiological, and hormonal responses during pre-slaughter handling in goats: a comparison between trained and untrained handlers - Kumar, Pavan; Abubakar, Ahmed Abubakar; Ahmed, Muideen Adewale; Hayat, Muhammad Nizam; Halim, Fakhrullah Abd; Rahman, Md Moklesur; Ajat, Mokrish; Kaka, Ubedullah; Goh, Yong-Meng; Sazili, Awis Qurni (Asian Australasian Association of Animal Production Societies, 2024)
Objective: The livestock handler attitude and their handling of animals is crucial for improving animal welfare standards, minimizing stress, improving productivity and meat quality. The present study was undertaken to assess the effect of training livestock handlers on behavioral, physiological, and hormonal responses during preslaughter handling in goats. Methods: A total of 6 handlers were divided into trained (trained in basic animal handling practices, animal behavior, and animal welfare), contact trained (not trained directly but interacted and saw the working of trained handlers), and untrained groups (no formal training). The handling experiment was conducted on 18 male goats by following a cross-over design. The goats were moved from lairage to slaughter point by trained, contact-trained, and untrained handlers. Various behavioral, physiological, and hormonal parameters were recorded at the lairage before handling and at the slaughter point after handling the goats. Results: The training of livestock handlers had a significant effect on behavioral, physiological, and hormonal responses in goats. The goats handled by untrained and contact-trained handlers were recorded with intense vocalization, significant (p<0.05) increase in heart rate and blood glucose, and catecholamines (adrenaline and nor-adrenaline), thereby indicating stress and poor animal welfare. The trained handlers were observed to use visual interactions (waving of hands or objects, blocking, hand raising, etc), and lower stress responses were recorded in the goats handled by this group. Conclusion: The present study highlights the importance of training to livestock handlers in improving animal welfare and minimizing stress in goats during pre-slaughter stress.